HUMOUR AS A COMPONENT OF LUDIC COMPETENCE DEVELOPMENT CRITERIA - Kobzieva, Iuliia (PSYCHOLOGICAL JOURNAL, 2020)
Based on theoretical analysis, the main specific features of humor are represented as scales of playfulness manifested in the complex relations of cognitive, affective, and conative aspects of humor include the following: humans have and develop a natural sense of humor on the basis of their playful attitude and formation of certain “habits”; humor as a “game with concepts” is revealed both as a human ability to understand and produce jokes; humor is a means of having fun peculiar for individuals with high playfulness, since they have an internal motive for merrymaking, a power to create a fun atmosphere, an active participation in it. Humor is embodied in beneficial humor styles related to well-being based on self-esteem and individual sense of happiness. An analysis of empirical studies of playfulness and humor styles revealed a link between playfulness and self-deprecating humor. In this context, it is necessary to take into account the internal (mood, self-confidence, values, etc.) and external resources (culture, environment, environment, context, etc.) of man. It can be assumed that the use of self-deprecating humor speaks more about the desire of a person (with a high level of playfulness) to cheer others than to humiliate himself. From which it can be concluded that black humor, or gallows humor, identified as an aggressive style of humor, as well as self-deprecating can be used as healthy humor, ie self-sustaining, as a tool of self-help and, therefore, can and should be directed exclusively at themselves. The criteria for the development of humor as a component of game competence are determined, as well as the corresponding groups of indicators: game competence in terms of sensitivity, lightness, imagination, flirtation, mischief, fusion; healthy styles of humor in terms of affiliative and self-supporting style of humor; emotional intelligence in terms of awareness of one's own feelings and emotions, management of one's own feelings and emotions, recognition of feelings and emotions of others, as well as management of feelings and emotions of other people; coping strategies on the indicators of problem solving planning, search for social support, acceptance of responsibility, positive reassessment; self-actualization in terms of time orientation, values ​​of self-actualization, view of human nature, the need for knowledge, creativity, spontaneity, contact, flexibility in communication; psychological well-being in terms of positive relationships, autonomy, environmental management, personal growth, goals in life, self-acceptance; actual abilities in terms of love, justice, directness (honesty), politeness.